The Trajectory of United Nations and Regional Organisations Peacekeeping in Africa: Theory and Practice - Aworawo, Friday (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
An increase in intra-state armed conflicts in Africa since independence has elicited the responses of the international community to resolve or manage them through the mechanism of peacekeeping operations initiated by the United Nations or regional organizations in Africa. The degrees of success or otherwise of peacekeeping operations has also varied. And since armed conflicts are inescapable, endemic and it’s also an integral part of human existence. then efforts at resolving them through peacekeeping are likely to endure. Hence, it is imperative to take a critical look at peacekeeping operations in Africa with a view to improve better performance in the future. It is against this background that this article examines the nature, pattern, impact and efficacy of the United Nations (UN), African Union (AU), Economic Community of West African States (ECOWAS), and the Southern African Development Community (SADC) peacekeeping operations in Africa and maintains that the prospect of successful peacekeeping operations in Africa lies in a tremendous collaboration between regional organizations in Africa and the United Nations. It concludes that the United Nations should provide required finance and expertise to complement Africans’ knowledge and mastering of the environment for successful future peacekeeping operations.